Formulation in DDA-MPLA-TDB Liposome Enhances the Immunogenicity and Protective Efficacy of a DNA Vaccine against Mycobacterium tuberculosis Infection - Tian, Maopeng; Zhou, Zijie; Tan, Songwei; Fan, Xionglin; Li, Longmeng; Ullah, Nadeem (Frontiers in Immunology, 2018)
Despite the vaccine, Mycobacterium bovis Bacillus Calmette Guérin (BCG) is used worldwide, tuberculosis (TB) remains the first killer among infectious diseases. An effective vaccine is urgently required. DNA vaccine has shown prophylactic as well as therapeutic effects against TB, while its weak immunogenicity hinders the application. As a strong inducer of Th1-biased immune response, DMT, consisting of dimethyldioctadecylammonium (DDA) and two pattern recognition receptor agonists monophosphoryl lipid A (MPLA) and trehalose 6,6'-dibehenate (TDB), was a newly developed liposomal adjuvant. To elucidate the action mechanism of DMT and improve immunological effects induced by DNA vaccine, a new recombinant eukaryotic expression plasmid pCMFO that secrets the fusion of four multistage antigens (Rv2875, Rv3044, Rv2073c, and Rv0577) of Mycobacterium tuberculosis was constructed. pCMFO/DDA and pCMFO/DMT complexes were then prepared and their physicochemical properties were analyzed. The immunogenicity and protection against M. tuberculosis infection in vaccinated C57BL/6 mice were compared. Formulation of DNA and two agonists into the DDA liposome decreased zeta potential but increased the stability of storage, which resulted in a slower and longer-lasting release of DNA from the DNA-DMT complex than the DNA-DDA liposome. Besides Th1 biased responses, pCMFO/DMT vaccinated mice elicited more significantly CFMO-specific IL2+ TCM cell responses in the spleen and provided an enhanced and persistent protection against M. tuberculosis aerosol infection, compared to pCMFO/DDA and pCMFO groups. Therefore, the adjuvant DMT can release DNA and agonists slowly, which might attribute to the improved protection of DMT adjuvanted vaccines. pCMFO/DMT, a very promising TB vaccine, warrants for further preclinical and clinical trials.